An Overview of Comprehensive Integration of Development Records and Nursing Documentation for Patients with Diabetes Mellitus - Suraya, Citra; Sansuwito, Tukimin bin; Dioso, Regidor III; Wisuda, Aris Citra (Yayasan Rumah Ilmu Professor, 2024)
Integrated patient development records form an integral part of nursing Integrated patient development records and Documentation, serving as a tangible representation of nurses' responsibility and accountability in executing their duties through interprofessional collaboration, while also offering authentic records of professional nursing care management. This study aims to elucidate the description of patient progress records and the completeness of nursing care Integrated patient development records and Documentation for Diabetes Mellitus patients in the Inpatient Ward of Siti Khadijah Islamic Hospital, Palembang. Employing a descriptive analytical approach with a cross-sectional design, the research involved purposive sampling, encompassing a total of 36 respondents. The findings revealed that among the respondents, 9 medical records (25%) were categorized as good, while 27 (75%) were classified as poor. Diagnosis results indicated that 28 medical records (77.8%) were deemed good, while 8 (22.2%) were rated as bad. Intervention records demonstrated that 3 respondents' medical records (8.3%) were assessed as good, whereas 33 respondents' records (91.7%) were categorized as poor. Implementation data showed that 26 respondents' medical records (72.2%) were in the good category, while 10 (27.8%) were in the bad category. Assessment outcomes showed that 5 respondents' medical records (13.9%) were considered good, while 31 (86.1%) were regarded as poor. Overall, Integrated patient development records and Documentation practices were observed among nurses in the inpatient ward at Siti Khadijah Islamic Hospital, Palembang; however, the implementation remains suboptimal. Statistical analysis of 36 medical records revealed that 24 (66.7%) were categorized as poor, whereas 12 (33.3%) were rated as good. Consequently, it is recommended to conduct standardized Integrated patient development records and Documentation training for both experienced and novice nurses, spanning across vocational and professional levels. Additionally, there is a necessity to establish and enhance nursing care instruments in alignment with standards, ensuring the optimal implementation of nursing process Integrated patient development records and Documentation